Cigarette smoke has sensory effects through nicotinic and TRPA1 but not TRPV1 receptors on the isolated mouse trachea and larynx - Kichko, Tetyana; Kobal, Gerd; Reeh, Peter (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2015)
Cigarette smoke (CS) exposes chemosensory nerves in the airways to a multitude of chemicals, some acting through the irritant receptors TRPV1 and TRPA1 but potentially also through nicotinic acetylcholine receptors (nAChR). Our aim was to characterize the differences in sensory neuronal effects of CS, gas phase, and particulate matter as well as of typical constituents, such as nicotine and reactive carbonyls. Isolated mouse trachea and larynx were employed to measure release of calcitonin gene-related peptide (CGRP) as an index of sensory neuron activation evoked by CS, by filtered CS gas phase essentially free of nicotine, and by dilute total particulate matter (TPM) containing defined nicotine concentrations. With CS stimulation of the superfused trachea, TRPV1 null mutants showed about the same large responses as wild-type mice, whereas both TRPA1(-/-) and double knockouts exhibited 80% reduction; the retained 20% response was abolished by mecamylamine (10 ?M), indicating a distinct contribution of nAChRs. These phenotypes were accentuated by using TPM to stimulate the immersed trachea; 50% of response was retained in TRPA1(-/-) and abolished by mecamylamine. In contrast, the gas phase acted like a sheer TRPA1 agonist, consistent with its composition, among other compounds, of volatile reactive carbonyls like formaldehyde and acrolein. In the trachea, the gas phase and CS were equally effective in releasing CGRP, whereas the larynx showed much larger CS than gas phase responses. Thus nicotinic receptors contribute to the sensory effects of cigarette smoke on the trachea, which are dominated by TRPA1. How this translates to human perception affords future research.
EVALuna2:2484